PENGGUNAAN LKS NON EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS XI IPA SMA 12 PEKANBARU - Yennita Yennita; Rury Septyowaty; Zulirfan Zulirfan (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2008)
The purpose of this research is to increase the result of student’s learning through using LKS nonexperimen with dynamic of rotation main material. Subject of this research is all students class XI IPA SMAN 12 Pekanbaru period 2008/2009. This research is experimentaly with research plan The static groupRandomized control-group only design, class XI IPA 1 be class control teach by convensional and XI IPA 2be class experiment, which teach by using LKS non-experimen for main lesson dynamic of rotation. Theresult which observe is cognitive domain through essay test. The result of this research show that studentsachievement, learning completeness, and completeness of the purpose class learning higher than classcontrol. It support by signification test between two class, that is the result of physic learning students whichteach by using LKS non-experimen is higher than the result of students learning by using convensional. Itshow from score thitung > ttabel the result thitung = 6,580 than ttabel (76; 0.05) = 1,665.Keyword: student’s achievement, LKS Non-Eksperimen